2019
DOI: 10.1186/s13104-019-4377-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of intestinal parasitic infections among patients attending Shahura Health Center, Northwest Ethiopia

Abstract: Objective Parasitic infections are the commonest infections affecting 3.5 billion people leading 450 million illnesses. Parasites are major public health problems in developing countries. This study was aimed to assess the prevalence and associated factors of parasitic infections among patients. A cross sectional study was conducted on 364 patients, attending Shahura Health Center, Northwest Ethiopia. Stool specimens were collected and examined using formol-ether concentration technique. Socio-dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 16 publications
11
48
7
Order By: Relevance
“…However, males were 3.1 and 1.5 times more likely to test positive for E. histolytica and G. lamblia than females, respectively (COR = 3.10 and 1.46). This nding is in agreement with other reports that showed that more males were infected with both parasites (18,21,22). The majority of the positive cases were also reported in females, who also had higher odds of being infected with E. histolytica and G. lamblia (4).…”
Section: Discussionsupporting
confidence: 93%
“…However, males were 3.1 and 1.5 times more likely to test positive for E. histolytica and G. lamblia than females, respectively (COR = 3.10 and 1.46). This nding is in agreement with other reports that showed that more males were infected with both parasites (18,21,22). The majority of the positive cases were also reported in females, who also had higher odds of being infected with E. histolytica and G. lamblia (4).…”
Section: Discussionsupporting
confidence: 93%
“…21,12,[22][23][24]5 However, our nding was lower than the prevalence reports from Cameroon 57.48%, 25 Kenya 50.9%, 26 Burkina Faso 73.3% 27 and some studies conducted in different parts of Ethiopia including Jimma 44.8%, 3 Jimma University Specialized Hospital 45.0%, 28 Hawassa 47.8% 7 and Shahura 56.9%. 9 This variation could be due to differences in socio-demographic characteristics, sample size differences and time period variation. Additionally, implementation of relevant health intervention programs and improvement of health service coverage with the active involvement of health extension workers in some places might contribute for this variation.…”
Section: Prevalence Of Intestinal Parasitesmentioning
confidence: 99%
“…Malnutrition, poor waste management, ignorance (illiteracy), unhygienic source of drinking water and depleted CD4 + counts (<200 cell/mm 3 ) among HIV/AIDS patients are the most common determinant factors for parasitic infections. 4,[7][8][9] The distribution of parasitic infection in developing countries is estimated to be as high as 95% among HIV infected patients. 10 In the same way as many other developing countries, particularly African countries, intestinal parasites are extensively distributed in Ethiopia; mainly associated with malnutrition, low socio-economic status, poor personal and environmental hygiene, food contamination and lack of potable water supply in rural and urban areas majorly resulted from inappropriate human excreta disposal systems and lack of awareness regarding common health promotion practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 550 million school children live in areas where intestinal parasitic infections (IPI) are endemic with 450 million of the illnesses occurring in sub-Saharan Africa (2,(4)(5)(6)(7). Parasitic infections are among the most preventable neglected tropical infections in humans (8).…”
Section: Introductionmentioning
confidence: 99%